Analysis of Students’ Ability in Solving Graph Problems - Dedek Faradilla; Rahmah Johar Johar (Proceedings of AICS - Social Sciences, 2017)
The importance of the problem-solving ability is to develop students’ comprehension in searching way out of a problem exposed. Therefore, this study was designed to analyze a further study regarding to the students’ ability in solving mathematic problems related to graphs (function and straight line equation). Still, it aimed at figuring out certain factors causing the phenomenon. This research was conducted at SMP Negeri 6 Banda Aceh and the participants involved in it were eighth-grade students with two kinds of instruments used, i.e. test and interview. Data obtained through the tests were analyzed by utilizing PISA scoring system in which one true answer scored one (1) and both unsolved and false answer scored zero (0). The results, then, were summed up altogether and the percentage of students’ correct answer for each question was analyzed later on. The result of the test revealed that students’ ability in solving mathematics problems related to graphs was low. This phenomenon was caused by some factors such as inadequate primary knowledge, insufficient understanding and unfamiliarity with the questions. Keywords: students’ ability, mathematics problem, graph.